Factors That Influence the Accountability of Village Fund Management with Individual Morality as a Moderating Variable - Dewi, Ni Putu Wina Purnama; Sujana, I Ketut; Gayatri, Gayatri; Ratnadi, Ni Made Dwi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Globalization is an opportunity and a challenge that must be faced by all citizens of the world, including Indonesia. The development of increasingly advanced information and communication technology will have a positive or negative impact on the sovereignty of a nation. In addition, globalization also makes access to information easier and faster to spread throughout the country, creating global transparency where the physical boundaries of a country's sovereignty are threatened with various disturbances and obstacles. This study uses a normative juridical approach aimed at knowing more about state defense education and its urgency in the era of society 5.0, so in order to maintain the integrity and sovereignty of the Indonesian state from various bad things caused by the development of globalization, through an integrated state defense approach in learning Citizenship at various levels of education in Indonesia is expected to foster the spirit of nationality for the next generation to always maintain the integrity of the unitary state of the Republic of Indonesia, because basically the effort to defend the country is an obligation for all citizens, which is carried out with full responsibility and is willing to sacrifice in service. to the state and nation, as for several important points contained in the concept of state defense including planning, governance, training management, learning methods, enrichment and deepening as well as real practices that can be developed in real life. nation and state, while the characteristics of students in practicing the concept of defending the state are maximizing time as good students and obeying all norms and laws that apply in Indonesia, then having good morals and attitudes, and balanced with noble national insight .